Some Aspects of Current Interruption Physics in High Voltage Circuit Breakers. Issue 2 (February 2014) - Seeger, M.; Galletti, B.; Bini, R.; Dousset, V.; Iordanidis, A.; Over, D.; Mahdizadeh, N.; Schwinne, M.; Stoller, P.; Votteler, T.
Abstract Recent results of experimental and theoretical investigations on current interruption processes are presented with a focus on SF6 high voltage circuit breakers. Various aspects of thermal interruption at the zero crossing of the current are shown, including the scatter and the distribution of arc voltage shortly before CZ and the role of turbulence. The thermal interruption capability of air and CO2 are compared to that of SF6. Investigations on the dielectric recovery are shown for SF6 and CO2. The breakdown voltage during the dielectric recovery can be described by simple streamer and leader inception models. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)